2013
DOI: 10.14791/btrt.2013.1.2.99
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Delayed Brain Metastasis from Renal Cell Carcinoma

Abstract: Brain metastasis occurs in 3.9-24% of patients with renal cell carcinoma (RCC), with an average interval from nephrectomy to brain metastasis of 1 to 3 years. A few cases have been reported where brain metastasis occurred after a delay of more than 10 years from the initial onset of renal cell carcinoma. This long interval for central nervous system metastasis from the primary cancer has been recognized as an indicator of better prognosis. Histopathological confirmation and aggressive treatment must be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The presence of brain metastases constitutes an important clinical feature to be considered, since kidney cancer tends to metastasize to the brain in about 4-11% of cases. 27,28 In this context, the panelists showed preference for cabozantinib over nivolumab, in accord with the data from the Nivoren trial that demonstrated the poor activity of nivolumab against untreated brain metastases in patients with cell clear RCC. 29 Moreover, real-world data showed that cabozantinib is safe and shows preliminary antitumor activity on brain metastasis of mRCC patients.…”
Section: Discussionmentioning
confidence: 56%
“…The presence of brain metastases constitutes an important clinical feature to be considered, since kidney cancer tends to metastasize to the brain in about 4-11% of cases. 27,28 In this context, the panelists showed preference for cabozantinib over nivolumab, in accord with the data from the Nivoren trial that demonstrated the poor activity of nivolumab against untreated brain metastases in patients with cell clear RCC. 29 Moreover, real-world data showed that cabozantinib is safe and shows preliminary antitumor activity on brain metastasis of mRCC patients.…”
Section: Discussionmentioning
confidence: 56%
“…In comparison, brain metastasis occurs in 3.9% to 24% of patients with RCC and is most frequently detected within an average of 1 to 3 years after the nephrectomy. [ 16 , 20 ] Similar to the cases of distant metastasis to other parts other than the brain, the prognosis of brain metastasis from RCC is poor; the median overall survival time after a diagnosis of brain metastasis was 10.7 months, and the 5-year survival rate was 12%. [ 20 ] To the best of my knowledge, a total of 20 cases of extremely delayed brain metastases from RCC have been reported in English so far, [ 2 17 ] making it a rare occurrence; all 21 cases including the present case are listed in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2 cases, the patients expired: 1 patient underwent total resection for a solitary metastatic lesion and expired due to systemic spread, [ 7 ] and the other underwent subtotal resection for multiple metastatic lesions and expired without systemic spread. [ 16 ] We present a case of systemic metastasis accompanied by lymph node metastasis at the time of brain metastasis diagnosis, although total resection and SRS were performed for a single lesion. In addition, Fukushima et al [ 2 ] reported that even in the case of multiple brain metastases, a good prognosis can be expected through total surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The host’s immune mechanism has been hypothesized to play an important role in this setting, regulating and influencing tumour growth [ 10 ]. Normally, RCC is slow growing in nature, and such slow growth of initially microscopic metastases might receive an acceleration when the host’s immune competency is compromised [ 3 ]. A case described by Cozar et al [ 4 ], where multiple late pulmonary metastases from a RCC treated 8 years earlier, developed only 2 months after an immunosuppressive treatment following renal transplant might give credit to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%